Secularity and public religion in Europe: Historical roots, theoretical debates and the case of public Islam - Salvatore, Armando (Hagar: Studies in Society and Culture, 2005)
This study builds on debates over the understanding of “secularity ” as a typically European construct, despite the diversity of institutional regulations of the religious field in various European countries and the existence of secular cultures "at large ” in non-European, including Islamic, worlds. The article locates the roots of this view of secularism in specific ruptures in the political and intellectual history of Europe, particularly during “the radical Enlightenment" (1650-1750). This idea of secularity and the concomitant concept of secularization have been challenged by Jose Casanova ’s attempts to redefine the conditions under which the “publicization " of religion not only allows, but actually requires secularity, if reinterpreted in a more elastic way: as the product of a transformation of religion’s modalities of access to the public sphere and not as the marker of religion’s inexorable privatization. Talal Asad ’s objections to this view of secularity ’s inherent malleability have generated a seminal debate, where the case of Islam in contemporary Europe has become a major terrain for testing views of secularity and public religion. The article attempts to conceptually mediate the discussion by looking at the conditions of Islam ’s publicization in todays Europe as part of a complex and sometimes contradictory trajectory of the transformation of secularity that older and newer secularization paradigms are insufficient to capture. It is at this crucial historical passage of the transformation of secularity that "public Islam " enters the stage and exerts pressures to redefine, though not to subvert, secularity.